2014
DOI: 10.1016/j.rmed.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of induced sputum measurements in moderate to severe asthma

Abstract: Sputum neutrophil percentage has good reproducibility in patients with moderate to severe asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…It is important to recognize a number of limitations of our study. Airway microbiology was assessed based on induced sputum, which, although shown to provide reproducible inflammatory cell levels in patients with moderate-to-severe asthma, 28,29 only provides an approximation of lower airway microbiology (in common with other lower airway sampling strategies). 30 It is also important to note that induced sputum levels of neutrophils and eosinophils can change frequently 31,32 and that the relationships between airway microbiology and inflammatory phenotype reported are cross-sectional.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to recognize a number of limitations of our study. Airway microbiology was assessed based on induced sputum, which, although shown to provide reproducible inflammatory cell levels in patients with moderate-to-severe asthma, 28,29 only provides an approximation of lower airway microbiology (in common with other lower airway sampling strategies). 30 It is also important to note that induced sputum levels of neutrophils and eosinophils can change frequently 31,32 and that the relationships between airway microbiology and inflammatory phenotype reported are cross-sectional.…”
Section: Discussionmentioning
confidence: 99%
“…Blood eosinophils were only measured during screening in ADEPT but published data suggest substantial variability even during a 24 h period [ 24 ] again raising the question as to whether eosinophilic asthma, defined by bEOS, is a stable phenotype. Fleming et al reported low reproducibility for sputum eosinophils in children [ 25 ] as did Rossall et al in adults with moderate to severe asthma [ 26 ]. In contrast Simpson et al found these measures to be stable in adults with stable asthma [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that estimates of repeatability of sampling have wide limits of agreement, of the same magnitude as the mean levels of neutrophils observed. 4 The present paper from Elliot et al reframes an interesting ques-tion about the precise origin of the cells contained in induced sputum samples. It has been suggested, logically, that induced sputum reflects the cells present in the large airways, 5 and further that elevated neutrophils are associated with more severe asthma.…”
mentioning
confidence: 89%